2021
DOI: 10.1007/s11250-021-02923-9
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium subsp. paratuberculosis (MAP) molecular diversity in cattle, sheep, and goats from Latin America and the Caribbean: a systematic review

Abstract: This study aimed to systematically collect and appraise the scientific evidence to answer the research question: What MAP genotypes have been isolated from cattle, sheep, and goats in Latin America and the Caribbean? An electronic search was conducted on three platforms (i.e., OVID®, Web of Science®, SciELO) as well as on the proceedings of the International Colloquium on Paratuberculosis. Inclusion and exclusion criteria were defined a priori and conserved through the systematic process and only articles publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
1
0
0
Order By: Relevance
“…MIRU-VNTR types INMV1 und INMV2 are predominant MAP genotypes isolated from cattle and goats in Europe, Canada, the United States, and several countries in Latin America [36,40,50,70,75,76]. Consistent with this, in the present study, INMV1 was found in almost all the samples from herd 1, and INMV2 was found in all the isolates from herd 2, in four isolates from two goats, and in one environmental sample in herd 1.…”
Section: Genotyping Resultssupporting
confidence: 89%
“…MIRU-VNTR types INMV1 und INMV2 are predominant MAP genotypes isolated from cattle and goats in Europe, Canada, the United States, and several countries in Latin America [36,40,50,70,75,76]. Consistent with this, in the present study, INMV1 was found in almost all the samples from herd 1, and INMV2 was found in all the isolates from herd 2, in four isolates from two goats, and in one environmental sample in herd 1.…”
Section: Genotyping Resultssupporting
confidence: 89%